The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1995
DOI: 10.1074/jbc.270.49.29469
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure of a γ Subunit of G Protein, γ12, and Its Phosphorylation by Protein Kinase C

Abstract: We have determined the primary structure of a novel ␥ subunit (␥ 12 , previously designated ␥ S1 ) of G protein purified from bovine spleen. The mature ␥ 12 protein composed of 68 amino acids had acetylated serine at the N terminus and geranylgeranylated/carboxylmethylated cysteine at the C terminus. This was consistent with the C-terminal prenylation signal in the amino acid sequence, which was predicted from ␥ 12 cDNA isolated from a bovine spleen cDNA library. Western blots with the specific antibody agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 50 publications
(57 reference statements)
3
75
0
Order By: Relevance
“…These observations are compatible with recent studies on immunological identification of both ␣ and ␤ subunits of trimeric G-proteins in the secretory granule fraction of normal rat islets and insulinoma tissue (22), and ␤TC3 cells (48), and provide further evidence for not only the presence of all three subunits of ␣␤␥ trimer on secretory granules, but also their (functional) regulation by carboxyl methylation (this study) and phosphorylation (32). Immunoblotting data indicated that at least four isoforms of ␥ subunits (i.e., ␥ 1 , ␥ 2 , ␥ 5 , and ␥ 7 ) are localized in pancreatic ␤ cells (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…These observations are compatible with recent studies on immunological identification of both ␣ and ␤ subunits of trimeric G-proteins in the secretory granule fraction of normal rat islets and insulinoma tissue (22), and ␤TC3 cells (48), and provide further evidence for not only the presence of all three subunits of ␣␤␥ trimer on secretory granules, but also their (functional) regulation by carboxyl methylation (this study) and phosphorylation (32). Immunoblotting data indicated that at least four isoforms of ␥ subunits (i.e., ␥ 1 , ␥ 2 , ␥ 5 , and ␥ 7 ) are localized in pancreatic ␤ cells (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…S. Mumby and A. G. Gilman (23). The antibodies against various ␥ subunits have been described previously (11,24). The isoform specificity and immunoprecipitation efficiency of antibodies used in this study are shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…The ␤␥ complex was also found to be involved in the stimulation of mitogen-activated protein kinase (3,4). So far, seven ␤ (from five separate genes and including two splice variants, ␤ 5L and ␤ 3S ) and 11 ␥ subunit isoforms have been found (1,(5)(6)(7)(8)(9)(10)(11). Different ␤␥ complexes do not have equivalent abilities to couple ␣ subunits to receptors or to regulate effectors.…”
mentioning
confidence: 99%
“…Recently, the ␥ 12 subunit has been shown to be a substrate for protein kinase C (12,13), suggesting that dimers containing this ␥ subunit may be subject to regulation by phosphorylation. The ␥ 12 subunit is widely expressed (12)(13)(14)(15) and, given the extensive role of the ␤␥ subunit in cell signaling (6,16), its phosphorylation may have important consequences. To examine the effects of ␥ 12 subunit phosphorylation on its activity, we purified recombinant ␤ 1 ␥ 12 dimers from baculovirus-infected Sf9 insect cells, phosphorylated them with PKC ␣ and ␤ 1 , and tested their activity in three assays of ␤␥ function.…”
mentioning
confidence: 99%